An integrative review of gift‐giving research in consumer behavior and marketing - Givi, Julian; Birg, Laura; Lowrey, Tina M.; Galak, Jeff (Journal of Consumer Psychology, 2023)
AbstractIn recent decades, scholars across all areas of marketing have studied consumer gift‐giving behavior. Despite the growing popularity of this research topic, no extensive review of the gift‐giving literature exists. To that end, this paper offers an expansive review of research on consumer gift‐giving, focusing primarily on work coming from within the marketing discipline, but also drawing on foundational pieces from other fields. We review extant scholarship on five of gift‐giving's most important aspects—givers' motivations, givers' inputs, giver‐recipient mismatches, value creation/reduction, and the greater gift‐giving context. In doing so, we illuminate the literature's key agreements and disagreements, shed light on themes that traverse ostensibly disparate gift‐giving findings, and develop deeper conceptualizations of gifting constructs. Moreover, we identify opportunities for improvement in the gift‐giving literature and use them to create key agendas for future gift‐giving research. In sum, this paper offers a single point of reference for gift‐giving scholars, improves academia's current understanding of gift‐giving, offers several theoretical contributions, and generates multiple paths for future research.